2008
DOI: 10.3390/ijerph5020086
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Silica Exposure Measurements at Two Zambian Copper Mines of Nkana and Mufulira

Abstract: We measured the quartz content of 20 bulk settled dust and 200 respirable dust samples in a cross-sectional dust exposure assessment that is part of an epidemiological study to ascertain the risk of nonmalignant respiratory diseases among Zambian copper miners. Dust samples were collected from the copper mines of Mopani Copper Mine plc (Mufulira and Nkana Mines). Analytical measurements employed NIOSH Method 0600 for gravimetric analysis of respirable dust and NIOSH Method 7500 for quartz analysis in bulk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Michelo et al [2] also reported that handling of tools and materials was the hazard most frequently causing injuries in a Zambian copper mine. Also in Zambia, Bwalya et al [3] found that limestone dust exposure was associated with increased prevalence of respiratory symptoms, and Hayumbu et al [4] reported that poor dust monitoring and control may increase the risk of non-malignant disease in miners.…”
Section: Introductionmentioning
confidence: 99%
“…Michelo et al [2] also reported that handling of tools and materials was the hazard most frequently causing injuries in a Zambian copper mine. Also in Zambia, Bwalya et al [3] found that limestone dust exposure was associated with increased prevalence of respiratory symptoms, and Hayumbu et al [4] reported that poor dust monitoring and control may increase the risk of non-malignant disease in miners.…”
Section: Introductionmentioning
confidence: 99%
“…The reported rates are mainly based on restricted sample sizes, making it difficult to derive population-based rates. Moreover, according to Hayumbu et al. (2008), the reported rates could substantially underestimate total silicosis cases in Zambia.…”
Section: Discussionmentioning
confidence: 96%
“…in most workplaces that have a potential for silica dust exposure, the concentration of silica dust exceeds the allowed occupational limits (Aliabadi et al, 2007, Gholami et al, 2012b, Golbabaei et al, 2004 In a study conducted by Hayumbu et al (2008) on two mines in Zambia, the silica levels in these mines were 59% and 26%, and the quantity of free silica dust was 0.992 and 0.888 mg/m 3 , which are all higher than the permissible exposure limit, but are still significantly lower than the silica dust levels observed in the present study. The silica contents measured in the present study are also higher than those reported in that study (Hayumbu et al, 2008). In a study performed by Golbabaei et al on the Senjedak building stone mine, the silica dust level was 0.67 mg/m 3 , which was higher than the exposure limit to silica dust in this study (Golbabaei et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The presence and quantity of free silica in mines and the occupational exposure of miners to silica dust have been the subject of many studies. Many of these studies have reported that, in most mines, the total and respirable dust levels are higher than the standard exposure limit (Golbabaei et al, 2004, Scarselli et al, 2014, Hayumbu et al, 2008, Azari et al, 2009. A study by Koo et al (2000) on the exposure to crystalline silica dust showed that the concentration of crystalline silica in the core-making unit was 0.023 mg/m 3 , which is lower than the limit, but in other units (molding, cleaning, melting) it was higher than the standard limits specified by the National Institute for Occupational Safety and Health (NIOSH) and ACGIH (Koo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%